Правове регулювання сервітутів на український землях в складі Російської імперії в кінці ХVIII – на початку ХХ ст. - Ковалик, Г.; Kovalyk, G. (Східноєвропейський національний університет ім. Лесі Українки, 2015)
У статті автор досліджує правове регулювання підстав та способів користування чужим майном за законодавством Російської імперії, що діяло на українських землях в кінці ХVIII – на початку ХХ століття. Право користування чужим майном регулювалося Зводом законів цивільних та рядом інших законів. У російському праві не існувало інституту речових прав на чуже майно, натомість право користування чужим майном розглядалося в межах інституту неповного права власності. Користуватися чужим майном можна було на підставі права участі загальної або приватної в користуванні та вигодах чужого майна, а також на підставі права угідь в чужому майні. The author studies legal regulations of the reasons and methods of using another's property under Russian legislation which operated on Ukrainian lands in the late 18-th – early 20-th cent. The right to use another's property was governed by the Civil Laws Compilation of Russian Empire and a number of others. In Russian legislature there was no institution regulating property rights over another's property, instead the right to use another's property was considered within the institution of partial ownership. The use of another's property was possible under the law of general or private participation in sharing another's property profits as well as to use lands in another location. The right of general ownership participation operated if all the profits of the property were shared equally among all the participants. Such legal regulation ought to be considered as a restriction of the property rights in favor of indefinite number of persons. The right of private ownership participation operated when the possibility to obtain benefits from the use of property had been established by law solely for the benefit of a particular owner. A part of chapter rules, regulating the rights of ownership participation, established the restrictions to the property rights, and the others settle servitude legal relations.
Legal Regulation of Servitudes on the Ukrainian Lands in Russian Empire in the Late 18-th – Early 20-th Cent
Keywords: сервітут; право участі загальної; право участі приватної; Звід Законів цивільних; право власності; servitude; right of general ownership participation; right of private ownership participation; Civil Laws Compilation of Russian Empire; property rights